2023
DOI: 10.1021/acssuschemeng.2c06706
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Synthesis of Ammonia Directly from Wet Air/N2 by Plasma Combined with a γ-Al2O3 Catalyst

Abstract: The conventional Haber−Bosch NH 3 synthesis process requires high temperatures and pressures, resulting in a high carbon footprint and the need to develop alternative NH 3 synthesis methods. Accordingly, plasma-based and γ-Al 2 O 3 -catalyzed NH 3 synthesis from H 2 O (a hydrogen source) and air/ N 2 (a nitrogen source) was studied under low temperature and low pressure conditions. The experimental results show that NH 3 can be synthesized with air/N 2 and H 2 O, although byproducts such as NO and N 2 O are al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Catalysts characterized by well-developed pore structures and high surface areas are favored, as they enhance the adsorption and capture of excited state particles within the plasma phase. [91] Research conducted by Zhang et al [33] and Nguyen et al [90] collectively underscores that, within the framework of plasma collectively revealed that in plasma catalysis, byproducts generated from the reaction between N 2 and water vapor predominantly manifest as N 2 O, while other forms of NOx remain below detectable thresholds. Notably, N 2 O production primarily occurs in the gas phase.…”
Section: Reaction Selectivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Catalysts characterized by well-developed pore structures and high surface areas are favored, as they enhance the adsorption and capture of excited state particles within the plasma phase. [91] Research conducted by Zhang et al [33] and Nguyen et al [90] collectively underscores that, within the framework of plasma collectively revealed that in plasma catalysis, byproducts generated from the reaction between N 2 and water vapor predominantly manifest as N 2 O, while other forms of NOx remain below detectable thresholds. Notably, N 2 O production primarily occurs in the gas phase.…”
Section: Reaction Selectivitymentioning
confidence: 99%
“…Additionally, Feng and his team‘s research suggests that the water vapor content significantly impacts energy efficiency and yield. When the water bath temperature increased from 30 °C to 90 °C, energy efficiency increased from approximately 4.4 mg ⋅ kWh −1 to about 7.5 mg ⋅ kWh −1 , and NH 3 production rate rose from around 2.6 μmol ⋅ g cat −1 ⋅ h −1 to approximately 4.3 μmol ⋅ g cat −1 ⋅ h −1 [91] …”
Section: Plasma‐assisted Synthesis Of Nh3 From N2 and H2omentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in the presence of • OH, 2hydroxy-piperazine (1) was subsequently formed, which underwent ring-opening oxidation to form [(2-aminoethyl)amino]acetaldehyde (2). However, [(2-aminoethyl)amino]acetaldehyde (2) was found to be unstable 29 and formed formaldehyde (8), oxalic acid (3), and ethylenediamine (4) by N−C bond breaking. The ethylenediamine continued to degrade to produce glycine (5) and ethanoic acid (6), which further produced oxalic acid (3) and formaldehyde, further forming formic acid (9).…”
Section: Rh Mn R H M Nmentioning
confidence: 99%
“…The main treatment methods for piperazine wastewater include physical, chemical, and biological methods. , Physical methods such as adsorption and precipitation can only separate piperazine from water and are prone to secondary contamination; in contrast, biological methods are prone to inactivation by poisoning, leading to their limited application . In recent years, advanced oxidation processes (AOPs) have been favored by many researchers due to their advantages including a fast reaction rate and final degradation products such as N 2 , CO 2 , and H 2 O. …”
mentioning
confidence: 99%